1996
DOI: 10.1128/mcb.16.1.414
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Specifies Chromosomal Localization of MeCP2

Abstract: MeCP2 is a chromosomal protein that is concentrated in the centromeric heterochromatin of mouse cells. In vitro, the protein binds preferentially to DNA containing a single symmetrically methylated CpG. To find out whether the heterochromatic localization of MeCP2 depended on DNA methylation, we transiently expressed MeCP2-LacZ fusion proteins in cultured cells. Intact protein was targeted to heterochromatin in wild-type cells but was inefficiently localized in mutant cells with low levels of genomic DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
232
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(248 citation statements)
references
References 29 publications
15
232
1
Order By: Relevance
“…24 However, it is unclear if this dichotomy depends on binding to methylated versus unmethylated sequences, despite abundant studies showing that MeCP2 preferentially binds to methylated DNA. 31 Nevertheless, the findings in this study favored the interpretation of a direct activator role for MeCP2 vis-à-vis the ␣-SMA gene in lung fibroblasts, which might be of importance in pathogenesis of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 50%
“…24 However, it is unclear if this dichotomy depends on binding to methylated versus unmethylated sequences, despite abundant studies showing that MeCP2 preferentially binds to methylated DNA. 31 Nevertheless, the findings in this study favored the interpretation of a direct activator role for MeCP2 vis-à-vis the ␣-SMA gene in lung fibroblasts, which might be of importance in pathogenesis of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 50%
“…The fact that doubling or tripling the levels of MeCP2 results in progressive neurological syndromes with increasing severity (MECP2 duplication and triplication syndromes, respectively) (6, 7) also raises questions about the binding patterns of MeCP2 and their functional consequences. Early studies found that MeCP2 interacts specifically with methylated cytosine in the CG context (mCG) (8)(9)(10). Recent in vivo studies in the adult mouse brain confirm the preference of MeCP2 for mCG over nonmethylated CG, although MeCP2 clearly binds widely across the entire genome (11).…”
mentioning
confidence: 99%
“…The functional signi®cance of methylation in this region and its e ect on binding has yet to be determined. However, methylation within non-CpG island regions is thought to contribute to the maintenance of a heterochromatinized state which precludes binding of transcription factors (Tate and Bird, 1993;Antequera et al, 1990;Nan et al, 1996). Since it has been shown that CpG dinucleotides in bulk chromatin outside CpG-islands may become hypomethylated in some tumours, altered methylation within this NF1 region could compromise the gene's structural integrity and alter NF1 expression (Gra et al, 1997).…”
Section: Discussionmentioning
confidence: 99%